2011
DOI: 10.1177/1523422311431220
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents to Employee Engagement

Abstract: The Problem. Employee engagement is an emerging concept in the HRD literature, with demonstrated organizational benefits; yet little is known about its antecedents. The purpose of this article is to explore conceptual and empirically driven antecedents as well as differentiate the two perspectives. The Solution. As a result of a structured literature review method, 42 antecedents were grouped by application at the individual and organizational level. The Stakeholders. HRD researchers seeking to conduct origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(121 citation statements)
references
References 45 publications
(75 reference statements)
3
117
0
1
Order By: Relevance
“…A review of the extant literature by Wollard and Shuck (2011) proposes that while there is some empirical research suggesting that a supportive organisational culture is an antecedent of employee engagement, such evidence is limited. However, one study by Oakley (2004) found that organisational culture provides a significant influence on the development of employee engagement.…”
Section: Engagementmentioning
confidence: 99%
“…A review of the extant literature by Wollard and Shuck (2011) proposes that while there is some empirical research suggesting that a supportive organisational culture is an antecedent of employee engagement, such evidence is limited. However, one study by Oakley (2004) found that organisational culture provides a significant influence on the development of employee engagement.…”
Section: Engagementmentioning
confidence: 99%
“…Conceptually, job involvement is a judgment; engagement is a psychological state (Saks, 2006). However, they have the propensity to share antecedents such as self-esteem and supervisory support and feedback and to be related to common organizational outcome variables such as performance and employee turnover (S. Wollard & Shuck, 2011), which perhaps is the impetus for the confusing state of affairs. A comparison of the definitions of the two constructs helps make clear that the focus of job involvement is on cognition (e.g., Lawler & Hall, 1970;Lodahl & Kejner, 1965;Kanungo, 1982;Paullay, Alliger, & Stone-Romero, 1994), whereas, engagement, according to most definitions (e.g., Baumruk 2004;Frank, Finnegan, & Taylor, 2004;Kahn, 1990;Richman, 2006;Shaw, 2005;Shuck & Wollard, 2010), encompasses cognition, emotion, and behavior.…”
Section: Job Attitude Variablesmentioning
confidence: 99%
“…Since then, various definitions, conceptualizations and measure have been forwarded in understanding the mechanisms that influence an employee to employ their discretionary effort to engage. Additionally, past proponents have found drivers and consequences of EE (Saks, 2006;Wollard & Shuck, 2011). However, to date the construct still suffers from construct ambiguity, especially due to its conceptualization and measure, between academia and the practitioner domain.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…However, to date the construct still suffers from construct ambiguity, especially due to its conceptualization and measure, between academia and the practitioner domain. Consequently, this has contributed to the current diffusion, where other researchers have now argued that EE is a passing fad (Wollard & Shuck, 2011), elusive construct (Saks, 2006) and a concept that should be ignored (Purcell, 2014).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation